6x+2=12x-10

Simple and best practice solution for 6x+2=12x-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+2=12x-10 equation:


6x+2=12x-10

We simplify the equation to the form, which is simple to understand
6x+2=12x-10

We move all terms containing x to the left and all other terms to the right.
+6x-12x=-10-2

We simplify left and right side of the equation.
-6x=-12

We divide both sides of the equation by -6 to get x.
x=2

See similar equations:

| y=-13x+45 | | 12x=7+5x | | K^2-1=-12k | | 5(3x-12)=x+115 | | z^3+(1-i)*z^2+(2i-1)*z+(i+3)=0 | | y=-13x+46 | | y^4+y^2+1=0 | | 4(3a-9)=84 | | h=(15/8)/(45/16) | | z^3+z^2-z+3=0 | | 6v^2-v=15 | | x+.33x=600000 | | 2x+3(x+6)=90 | | 4x-(4-2x)=5x | | .33x=600000 | | 30=(3w-1)w | | 4x^2-65=-7x | | 4x-(4-4x)=5x | | 4x-(4-3x)=5x | | 0.4X+0.6=-0.6-0.2X | | 5x+14x=180 | | (X+(0.10X))+(Y+(0.04Y))=523 | | g=(12/25)/(6/50) | | 36x^2-x^2=62 | | (4x+1)(2x+6)=0 | | 15x-5=13x-9 | | 3k^2=28+8k | | 3w-45=42 | | 5q-8=-2q+48 | | 16x+24y=20 | | 7x-1=1-7x | | -6=14+x |

Equations solver categories